(untitled) (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
Artisan fishers of Osodo beach of Sondu-Miriu River (Kenya) use both traditional and modern gear to catch riverine fish species. This study, conducted between August 2006 and July 2007, revealed that fishers most predominantly used gear were the seine nets (42%) and the gill nets (28%). Other used gear include long lines (14%); fish baskets (9%) and weirs (7%). The selectivity of this fishing gear varied with the developmental stages of the fish to be caught. Non-selective gear caught both targeted and non-targeted species irrespective of size and development stages. The ranking of selective to non-selective fishing gear was the long lines, fish baskets, weirs, gill nets and beach nets at 2%, 11%, 16%, 24% and 32%, respectively. The non-selective fishing gear may have negative impacts on the riverine fish by reducing spawning biomass and lacustrine fish recruitment. These findings underscore the need for greater appreciation, research, and adaptation of appropriate fishing gear to ensure sustainable utilization of the riverine fisheries in Sondu-Miriu River DOI: http://dx.doi.org/10.3126/hn.v15i0.11301 HYDRO Nepal Journal Journal of Water Energy and Environment Volume: 15, 2014, July Page: 82-86